Liability rule failures? Evidence from German court decisions - Annika Pape (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
Since 2007, all insurance intermediaries face negligence liability that is supposed to reallocate risks and set economic incentives. Nonetheless, further measures are taken to improve consumer protection. So, the question arises does the liability rule influence the agents behavior, or not, and does it influence in the intended way, or not? Do court cases provide evidence for failure of the current liability rule? Based upon an economic analysis of liability rules, aspects concerning potential failures can be derived. An analysis of twelve verdicts suggests that understatement of intermediary responsibility as well as a potential overstatement of the consumer responsibility yields suboptimal results. Often, missing documentation reinforces that tendency.
Keywords: G22; D83; D89; K29; K40; 330; Insurance; Intermediaries; Liability; Consumer Protection; Court Errors; Court Cases